New exact solutions for generalized Gardner equation - Demiray, Seyma T.; Bulut, Hasan (Academic Publication Council, 2017)
In this research, we seek exact solutions of generalized Gardner equation. We make use of extended trial equation method to attain exact solutions of generalized Gardner equation. Firstly, we find some exact solutions such as soliton solutions, rational, Jacobi elliptic and hyperbolic function solutions of generalized Gardner equation by the help of extended trial equation method. Then, for some parameters, we draw two and three dimensional graphics of imaginary and real values of some exact solutions that we acquired by using this method.
Keywords: Extended trial equation method; generalized Gardner equation; hyperbolic function solutions; Jacobi elliptic solutions; soliton solutions; rational solutions